Narrative Case Notes Have the Potential to Predict Seclusion 3 Days in Advance: A Mixed-Method Analysis - Stepanow, Clara; Stepanow, Jefim; Walter, Marc; Borgwardt, Stefan; Lang, Undine E.; Huber, Christian G. (Frontiers in Psychiatry, 2019)
Objectives. Current risk assessment tools can predict problematic behavior and the need for coercive measures, but only with a moderate level of accuracy. The aim of this study was to assess antecedents and triggers of seclusion. Methods. Narrative notes of health care professionals on psychiatric inpatients were analyzed daily starting three days prior to seclusion in the case group (n=26) and compared to a matched control group without seclusion (n=26) by use of quantitative and qualitative research methods, based on qualitative content analysis. Results. Quantitative measures showed more aggression in the case group with highly significant differences between the groups (p<.001) at all measurement times. Seclusion was significantly associated with the total word count of the narrative notes. Subjective emotional expressions by staff were more apparent before seclusion (p=.003). Most frequently, subjective expressions regarding 'arduous/provocative' (p<.001) and 'anxious' (p=.010) sentiments could be identified in the case group. Description of patients' behavior in the case group included more negatively assessed terms (p=.001). Moreover, sleep loss, refusing medication, high contact frequency, demanding behavior and denied requests were present in a significantly higher frequency before seclusion. Expressions like 'threatening' (p=.001) were found only before seclusion and appeared to have the function of personal risk assessment. The expression 'manageable' (p=.035) appeared often in difficult situations that could still be handled. Conclusion. Several factors preceding seclusion could be identified. Narrative notes of staff already showed differences three days before the escalation. Particularly the word count, the analysis of terms describing patients' behavior, subjective expressions of staff, and terms used as a function of personal risk assessment could help to provide better predictions of aggressive incidents and to prevent coercive measures.